Short Stay EVAR is Safe and Cost Effective. (March 2019) - Shaw, Sarah E.; Preece, Ryan; Stenson, Katherine M.; De Bruin, Jorg L.; Loftus, Ian M.; Holt, Peter J.E.; Patterson, Benjamin O.
Abstract : Objective: Reducing length of stay (LOS) following surgery offers the potential to improve resource utilisation. Endovascular aneurysm repair (EVAR) is now delivered with a low level of morbidity and as such may be deliverable as a "23 hour stay" intervention. This systematic review aims to assess safety, feasibility and cost effectiveness of a short stay EVAR pathway. Methods: A database search of Ovid MEDLINE (1996 – April 2018) and Embase (1974 – April 2018) was completed. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used. A Newcastle–Ottawa Scale was applied to assess study bias. Results: In total, 570 papers were identified through the literature search, of which 32 abstracts were screened. This led to nine papers being assessed for eligibility. From five suitable studies, 450 (75%) patients were successfully discharged the same or next day after EVAR. Complications most often occurred within 3 hours of surgery, and major complications requiring intensive treatment unit admission occurred within 6 hours. Readmission rates were 0–5% for those discharged early, with no difference in 30 day readmission. Early discharge led to a statistically significant cost saving of £13, 360 (LOS four days) to £9844 (LOS one day). Conclusion: Selected patients can safely undergo EVAR using a short stay pathway. A period of monitoring 6 h post-operatively for low risk patients would be sufficient. Reducing length of stay after EVAR in the UK from the current median of three days to 1.5 days would free 4361 bed days and lead to a saving of approximately £1, 800, 000 annually.